The Dangerous Effects of Tramadol Abuse: Literature Review - Prasetyo, Fajar; Indah Laily Hilmi (Jurnal EduHealth, 2022)
Drug abuse is an act of using one or a combination of drugs in relatively high doses with the aim not for medication but to achieve a pleasure without regard to other aspects. Drug abuse can be motivated by several factors such as a weak personality, a high sense of curiosity, peer invitations, social problems and pressures, and the ease with which drugs can be obtained at low prices. One of the drugs that is often abused is tramadol. This is because tramadol can provide a euphoric effect. Without realizing it, tramadol abuse actually causes other, more dangerous effects. Therefore, writing this review article aims to provide an overview of other effects resulting from the abuse of tramadol drugs. The writing of this article review uses a systematic review method in which data is taken from national and international scientific articles or journals with a limitation of publication in the last 10 years. Articles obtained from searches using Google Scholar, PubMed, and Science Direct. From the results of the review, it is known that the misuse of tramadol drugs can be fatal because it can cause vomiting, seizures, sedation, and even death. Not only that, tramadol in high doses also affects fertility factors such as sperm defects and erectile dysfunction. Special attention is needed for cases of tramadol abuse because most of these activities are carried out by teenagers.